SOME NOTEWORTHY USES OF ει OR ει IN HELLENISTIC GREEK, WITH A NOTE ON ST MARK viii 12 - Coleman, N. D. (The journal of theological studies, 1927)
N. D. COLEMAN; SOME NOTEWORTHY USES OF ει OR ει IN HELLENISTIC GREEK, WITH A NOTE ON ST MARK viii 12, The Journal of Theological Studies, Volume os-XXVIII, Issu